1976
DOI: 10.1111/j.1365-2427.1976.tb01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diel periodicity in the drift of aquatic insects in a subtropical Florida stream

Abstract: A study of insect drift was conducted in a small, subtropical Florida stream from December 1971 to December 1972 to describe the seasonal and diel periodicity and to determine factors influencing behavioural drift. Paired samples of 2h duration beginning 15 min after sunset were taken biweekly, and hourly collections over a 24-h period were made quarterly. Benthic invertebrates were collected on each date from three habitats (riffle, pool and aquatic vegetation) and temperature, dissolved oxygen and current ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
(25 reference statements)
3
34
1
Order By: Relevance
“…However, we found higher drift densities in the dry winter season than in the wet summer season (Fig. 3(A)), corroborating the findings of Cowell and Carew (1976) and Schreiber (1995). Furthermore, we observed significant differences in taxonomic composition between seasons (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, we found higher drift densities in the dry winter season than in the wet summer season (Fig. 3(A)), corroborating the findings of Cowell and Carew (1976) and Schreiber (1995). Furthermore, we observed significant differences in taxonomic composition between seasons (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…2). We believe that different life history patterns related to the marked differences in environmental conditions (e.g., temperature, photoperiod, patterns of allochtonous input) found between the seasons are probably responsible for the differences in seasonal drift patterns that we observed (Cowell and Carew, 1976). The main difference between wet and dry seasons was the density of Simuliidae.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…It is most likely that formation of new islands (i.e. channel reconstruction and restoration) would occur during summer months, periods of high invertebrate drift (Cowell & Carew 1976;Stoneburner & Smock 1979). Little contribution from upstream migration would occur until several months after water was flowing in the channel.…”
Section: Resultsmentioning
confidence: 99%
“…Although neither of these taxa is immune from predation, they appear to suffer markedly lower predation pressure than do larger invertebrates. In an intriguing study of a subtropical stream in Florida, Cowell and Carew (1976) found a shift from no periodicity to nocturnal drifting in PolypediZum haterale when late instars predominated. Anderson and Lehmkuhl (1968) found the mean weight of drifting individuals in four groups (Chironomidae, Baetis, Paraleptophlebia, Capnia) to be greater by night than by day.…”
Section: Invertebratesmentioning
confidence: 99%